Antennal Transcriptome Analysis of the Chemosensory Gene Families From Trichoptera and Basal Lepidoptera - Yuvaraj, Jothi Kumar; Andersson, Martin N.; Zhang, Dan-Dan; Löfstedt, Christer (Frontiers in Physiology, 2018)
The chemosensory gene families of insects encode proteins that are crucial for host location, mate finding, oviposition, and avoidance behaviors. The insect peripheral chemosensory system comprises odorant receptors (ORs), gustatory receptors (GRs), ionotropic receptors (IRs), odorant binding proteins (OBPs), chemosensory proteins (CSPs) and sensory neuron membrane proteins (SNMPs). These protein families have been identified from a large number of insect species, however they still remain unidentified from several taxa that could provide important clues to their evolution. These taxa include older lepidopteran lineages and the sister order of Lepidoptera, Trichoptera (caddisflies). Studies of these insects should improve evolutionary analyses of insect chemoreception, and in particular shed light on the origin of certain lepidopteran protein subfamilies. These include the pheromone receptors (PRs) in the “PR clade”, the pheromone binding proteins (PBPs), general odorant binding proteins (GOBPs), and certain presumably Lepidoptera-specific IR subfamilies. Hence, we analyzed antennal transcriptomes from Rhyacophila nubila (Trichoptera), Eriocrania semipurpurella and Lampronia capitella (representing two old lepidopteran lineages). We report 37 ORs, 17 IRs, 9 GRs, 30 OBPs, 7 CSPs, and 2 SNMPs in R. nubila; 37 ORs, 17 IRs, 3 GRs, 23 OBPs, 14 CSPs, and 2 SNMPs in E. semipurpurella; and 53 ORs, 19 IRs, 5 GRs, 29 OBPs, 17 CSPs, and 3 SNMPs in L. capitella. We identified IR members of the “Lepidoptera-specific” subfamilies IR1 and IR87a also in R. nubila, demonstrating that these IRs also occur in Trichoptera. Members of the GOBP subfamily were only found in the two lepidopterans. ORs grouping within the PR clade, as well as PBPs, were only found in L. capitella, a species that in contrast to R. nubila and E. semipurpurella uses a so-called Type I pheromone similar to the pheromones of most species of the derived Lepidoptera (Ditrysia). Thus, in addition to providing increased coverage for evolutionary analyses of chemoreception in insects, our findings suggest that certain subfamilies of chemosensory genes have evolved in parallel with the transition of sex pheromone types in Lepidoptera. In addition, other chemoreceptor subfamilies show a broader taxonomic occurrence than hitherto acknowledged.